Distribution of Cocoa Pod Borer (CPB) Conopomorpha cramerella (Snellen) (Lepidoptera: Gracillariidae) egg population with respect to the Pod Phenology - Mohd Ali, Noorazlin; Syed Hassan, Syed Tajuddin; Ismail, Azhar (Universiti Putra Malaysia Press, 2005)
At the Malaysian Cocoa Board Research Station at Hilir Perak, Sg. Sumun, Perak, an in-depth investigation on sampling of the cocoa pod borer (CPB) was conducted over a period of 12 months from 2000 to 2001. Several components were examined including determining distribution of CPB with respect to pod phenology and determining optimum sample size to produce sampling parameters for CPB using three different sampling techniques, random, systematic and stratified. Data were analysed using two aggregation models; Taylor's Power Law (b coefficient) and Iwao's mean crowding (f3 coefficient). CPB's egg were found to be highly aggregated. In determining optimum sample sizes, two parameters were calculated; b coefficient of Green's model and f3 coefficient for Kuno's model. The Green model was suitable to produce the most efficient sampling sizes during low and high population densities for all sampling techniques.